Preview of preventive maintenance practices and teamwork initiative in workplace - Mad Lazim, Halim; Lamsali, Hendrik; Salleh, Mohamed Najib (Medwell Journal, 2016)
The aim of this research is to present the findings from a case study conducted on the role of teamwork towards maintenance performance in a Malaysian manufacturing plant.However, the company lack of strategy in implementing maintenance initiatives affected its performance in terms of quality problems and escalating cost.Preventive maintenance helps to reduce the rate of equipment failure and to enhance equipment life.Preventive maintenance impacts on quality, safety, cost, capacity and environment.The study was conducted to identify role of teamwork toward maintenance performance in a manufacturing company.The data was gathered from interviews conducted on a few key personnel of the company.The role of teamwork influenced the maintenance performance of the company.The main contribution of the study is an understanding of the role of teamwork toward maintenance performance.